Implementation of Guidance and Counseling in Preventing Bullying: The Role of Teachers in Junior High Schools - Vera Yuliza; Nurussakinah Daulay (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2023)
This research aims to describe bullying behavior and the function of guidance and counseling instructors in avoiding bullying in kids. The qualitative research descriptive technique was applied through observation, interviews, and recording. Guidance and counseling instructors, bullying behavior students, and bullying victim students from public junior high schools in Medan City were the topics of this study. This study's data analysis includes the data reduction step, data presentation, and findings. According to the findings of this study, verbal bullying happens in various educational settings, such as flinging foul words, spreading ugliness, providing nicknames, and blaming. The role of guidance and counseling teachers is to carry out guidance and counseling activities in schools to prevent bullying by providing individual counseling services, information services about bullying behavior, the impact of bullying behavior, and preventive, curative, and preservative actions. Following up on the findings of this study, the function of guidance and counseling instructors in avoiding bullying must be enhanced through programs aimed at employing guidance and counseling services in preventative activities.